2013
DOI: 10.1111/jph.12200
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Molecular Characterization of a 16SrII‐A* Phytoplasma in Grapefruit (Citrus paradisi) with Huanglongbing‐like Symptoms in China

Abstract: In the year 2010, in a survey in Guangxi Province, China, to detect and characterize phytoplasmas in a huanglongbing (HLB)-infected grapefruit (Citrus paradisi) orchard, 87 leaf samples with symptoms of blotchy mottle were collected from symptomatic grapefruit trees, and 320 leaf samples from symptomless trees adjacent to the symptomatic trees. Nested polymerase chain reaction (PCR) using universal phytoplasma primer set P1/ P7 followed by primer set fU5/rU3 identified 7 (8.0%) positive samples from symptomati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 29 publications
1
22
0
1
Order By: Relevance
“…Although the disease is primarily attributed to 'Candidatus Liberibacter asiaticus', an unculturable α-proteobacterium, phytoplasmas belonging to the groups 16SrIX in Brazil (Texeira et al, 2008), 16SrII in China (Lou et al, 2014), and 16SrI in China (Chen et al, 2009) Liberibacter asiaticus' was tested by real-time PCR (ABI 7300, Applied Biosystems, USA) using specific16S rDNA-based TaqMan primer-probe sets (HLBasr/HLBp) (Li et al, 2006). To ascertain the association of phytoplasma, PCR was performed using P1/P7 universal primers specific to the 16S rRNA gene of phytoplasmas, followed by a nested PCR from a 1:30 dilution of the P1/P7 PCR products using primer sets R16F2n/R16R2 (Gundersen & Lee, 1996) and Fu5/Ru3 (Lou et al, 2014).…”
Section: Figurementioning
confidence: 99%
“…Although the disease is primarily attributed to 'Candidatus Liberibacter asiaticus', an unculturable α-proteobacterium, phytoplasmas belonging to the groups 16SrIX in Brazil (Texeira et al, 2008), 16SrII in China (Lou et al, 2014), and 16SrI in China (Chen et al, 2009) Liberibacter asiaticus' was tested by real-time PCR (ABI 7300, Applied Biosystems, USA) using specific16S rDNA-based TaqMan primer-probe sets (HLBasr/HLBp) (Li et al, 2006). To ascertain the association of phytoplasma, PCR was performed using P1/P7 universal primers specific to the 16S rRNA gene of phytoplasmas, followed by a nested PCR from a 1:30 dilution of the P1/P7 PCR products using primer sets R16F2n/R16R2 (Gundersen & Lee, 1996) and Fu5/Ru3 (Lou et al, 2014).…”
Section: Figurementioning
confidence: 99%
“…; Lou et al. ). The phytoplasma related to the pigeon pea witches' broom (PPWB) phytoplasma (16Sr IX) was found in sweet orange trees closely associated with HLB symptoms in São Paulo, Brazil, in 2008.…”
Section: Discussionmentioning
confidence: 97%
“…() and Lou et al. () in China recently reported that phytoplasmas are associated with HLB symptoms. However, no phytoplasma was found in HLB‐diseased citrus trees and in psyllids collected from Florida (Meyer and Hoy ; Sagaram et al.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…P. asteris (Chen et al., ) and Ca . P. aurantifolia (in China) (Lou et al., ), Ca . P. asteris (in Mexico) (Arratia‐Castro et al., ) and Ca .…”
Section: Introductionmentioning
confidence: 99%